Do Statins Affect Viral Infections Encountered by International Travelers? - Chinmay T. Jani; Christian Mouchati; Nour Abdallah; Ruchi Jani; Loukas Kakoullis; Lin H. Chen (Tropical Medicine and Infectious Disease)
Statins are among the most frequently prescribed medications. In addition to their well-established effectiveness in lowering total cholesterol, LDL, and triglycerides, statins have been described to have immunomodulatory and anti-inflammatory properties and have been associated with improved endothelial functions. Given the common use of statins, we sought to evaluate the effect of statins on some viral infections encountered by residents in tropical areas or by international travelers. A literature search was performed in PubMED/MEDLINE focusing on keywords that included statins and the viruses of interest, including SARS-CoV-2, influenza, yellow fever, dengue, Zika, tick-borne encephalitis, hemorrhagic fever viruses, hepatitis A, norovirus, hepatitis B, hepatitis C, measles, and herpesviruses; findings were synthesized for each virus into a summary. The effects of statins on viral infections vary depending on the specific virus. While some studies indicate potential benefits in chronic HBV and HCV infections, evidence regarding SARS-CoV-2 and influenza remains inconclusive due to mixed findings from observational studies and randomized controlled trials. The role of statins in other viral infections is largely unexplored, with preclinical data available for only a few viruses. Given the conflicting evidence, further prospective studies and randomized controlled trials are warranted to elucidate statins’ role in viral infections, particularly in modulating inflammation, endothelial dysfunction, and immune responses. Future research should aim to define the optimal patient populations, target viruses, statin types, and treatment durations that may confer benefits in specific viral infections.